Optimalisasi Partisipasi Politik Penyandang Disabilitas di Kabupaten Lamongan - Rosyid, Halimur (Jurnal Review Politik, 2020)
This study aims to understand the phenomenon of low political participation in Lamongan Regency. This research was conducted by identifying various inhibiting factors for political participation of persons with disabilities, and by explaining what factors play a role in its optimization. The method used in this research is a qualitative approach (qualitative methods) which refers to various techniques in research; participatory research, intensive personal interviews, observation process and focus group discussions (FGD) to understand the experiences of key informants. The results of this study indicate that the inhibiting factors for political participation of persons with disabilities is the lack of political participation accessibilityfor persons with disabilities, as well as the charity view that considers persons with disabilities as marginalized people who need a helping hand. Meanwhile, the optimization of the role and political participation of persons with disabilities is carried out by drafting a regional regulation on the implementation of protection and fulfillment of the rights of persons with disabilities by the Executive and DPRD (Regional House of Representatives)Lamongan, as well as by strengthening the socialization intensitycarried out by the general election organizer, namely the KPUD (Regional General Election Commission) Lamongan.